Antimalarial and cytotoxic activities of ethnopharmacologically selected medicinal plants from South Vietnam. - Nguyen-Pouplin, J; Tran, H; Tran, H; Phan, T; Dolecek, C; Farrar, J; Tran, T; Caron, P; Bodo, B; Grellier, P (2007)
Malaria is a major global public health problem and the alarming spread of drug resistance and limited number of effective drugs now available underline how important it is to discover new antimalarial compounds. An ethnopharmacological investigation was undertaken of medicinal plants traditionally used to treat malaria in the South Vietnam. Forty-nine plants were identified, 228 extracts were prepared and tested for their in vitro activity against Plasmodium falciparum, and assessed for any cytotoxicity against the human cancer cell line HeLa and the embryonic lung MRC5 cell line. In a first screening at a concentration of 10 microg/ml, 92 extracts from 46 plants showed antiplasmodial activity (parasite growth inhibition >30%). The IC(50) values of the most active extracts were determined as well as their selectivity towards Plasmodium falciparum in comparison to their cytotoxic effects against the human cell lines. Six plants showed interesting antiplasmodial activity (IC(50) ranging from 0.4 to 8.6 microg/ml) with a good selectivity: two Menispermaceae, Arcangelisia flava (L.) Merr. and Fibraurea tinctoria Lour., and also Harrisonia perforata (Blanco) Merr. (Simaroubaceae), Irvingia malayana Oliv. ex Benn. (Irvingiaceae), Elaeocarpus kontumensis Gagn. (Elaeocarpaceae) and Anneslea fragrans Wall. (Theaceae).